Quality of life and urban size - Vicente Royuela; Jordi Suri\~nach (European Regional Science Association (ERSA), 2005)
Optimal City Size Theory has been superseded by new paradigms, such as the supply-oriented dynamic approach or the city network. Nevertheless, several aspects remain to be considered. First, the quality of life concept, which in many models enters into utility functions of households, can be addressed in a different way. Secondly, the bi-directional relationship between amenities and disamenities on the one hand and city size on the other needs to be considered. Both these points are empirically tested with instrumental variables in a local dynamic framework, the 314 municipalities belonging to the province of Barcelona (Spain), in the period 1991-2000.
Keywords: 330